Implementasi Hukum Ekonomi Syariah dalam Sistem Perbankan Syariah di Indonesia: Analisis Regulasi dan Etika - Jaelani, Jaja (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research examines the application of Sharia economic law in the Islamic banking system in Indonesia, focusing on regulatory and ethical aspects. Through a qualitative approach that utilizes literature studies, regulatory document analysis, and case studies of several Islamic banks, this research aims to identify how the principles of Islamic economics are translated into banking practices as well as the challenges and opportunities faced. The research results indicate that the application of the principles of justice, transparency, and the prohibition of usury positively contributes to customer trust and the stability of the financial system, although there are still challenges related to the synchronization of regulations and the consistent interpretation of Sharia principles.